Management of contraception and unwanted pregnancy of dogs raised in human settlements in the Ventanilla district, Peru - Ponte, Kyara (2022)
The aim of this study was to describe the perceptions and practices of dog owners about the management of contraception and unwanted pregnancy of dogs raised in human settlements in the district of Ventanilla, Callao-Peru. An observational, descriptive and cross-sectional investigation was carried out based on surveys applied to dog owners in 13 human settlements of the district. The variables studied were contraception practices in dogs, management of unwanted pregnancy, fate of these offspring in the community and consequences of the lack of reproductive control in dogs. In 400 answered surveys, a total of 828 dogs (452 males and 376 females) were reported. Of these, 6% of males and 26.1% of females were castrated and spayed, respectively. The main reasons for accepting to neuter/sterilize the dog was the desire not to have more animals and to avoid an excess population of dogs. Instead, the main reason for not accepting surgical reproductive control was the scarcity of financial resources. Fifty-eight percent of those surveyed were willing to perform surgical reproductive control on dogs, regardless of the sex of the animal. Regarding the fate of the offspring of female dogs with unwanted pregnancy, 87.4% of the owners mentioned that they would give them up for adoption, but 71.8% mentioned that most of the members of the community abandoned the offspring. The main consequences of the presence of stray dogs recognized by the respondents were the impact on animal welfare due to illness, malnutrition or accidents (40.8%) and the increase in environmental contamination by faeces and garbage dispersion (37.3%). It is concluded that it is necessary to develop campaigns for responsible ownership of companion animals in this population to safeguard animal welfare and public health.